The widening military-political gap in Israel: Former chiefs of staff fight for principles of statism - Yoram Peri (Stiftung Wissenschaft und Politik (SWP), 2020)
Over the last decade, the gap between the military and political elites in Israel has increased and eventually peaked in 2019, when a group of senior officers who had just retired from the Israel Defense Forces (IDF) formed a new party - led by three former chiefs of staff - and called for the replacement of Prime Minister Benjamin Netanyahu's government. This gap has developed because Israel's previous governments have represented a new kind of polarising, right-wing politics beyond what is considered a shared national common sense. The military, on the other hand, is striving to maintain the character it has acquired as a 'Nation in Arms' by reflecting the entire society of Israel and acting according to its professional ethos and national statist values. The stated goal of the officers entering politics was to defend those values against perceivably partisan and polarising governmental politics. The composition of a future government is thus both: A competition over principled values of the state, but also a determination about the steps regarding the military and political leadership in Israel, as well as the military's relations with society at large.
Keywords: 320